Statistics with R a beginner's guide - Stinerock, Robert Noel (London ; Thousand Oaks, California SAGE, 2018)
The dynamic, student focused textbook provides step-by-step instruction in the use of R and of statistical language as a general research tool. It is ideal for anyone hoping to: Complete an introductory course in statistics Prepare for more advanced statistical courses Gain the transferable analytical skills needed to interpret research from across the social sciences Learn the technical skills needed to present data visually Acquire a basic competence in the use of R. The book provides readers with the conceptual foundation to use applied statistical methods in everyday research. Each statistical method is developed within the context of practical, real-world examples and is supported by carefully developed pedagogy and jargon-free definitions. Theory is introduced as an accessible and adaptable tool and is always contextualized within the pragmatic context of real research projects and definable research questions.
1. Introduction and R Instructions -- 2. Descriptive Statistics: Tabular and Graphical Methods -- 3. Descriptive Statistics: Numerical Methods -- 4. Introduction to Probability -- 5. Discrete Probability Distributions -- 6. Continuous Probability Distributions -- 7. Point Estimation and Sampling Distributions -- 8. Confidence Interval Estimation -- 9. Hypothesis Tests: Introduction, Basic Concepts, and an Example -- 10. Hypothesis Tests About Means and Proportions: Applications -- 11. Comparisons of Means and Proportions -- 12. Simple Linear Regression -- 13. Multiple Regression.
Includes index
Keywords: Statistics -- Data processing; R (Computer program language); Statistics -- Computer programs; 54.53 programming languages